2015
DOI: 10.1037/a0038993
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and integrative tests of family stress model effects on Mexican origin adolescents.

Abstract: The family stress model represents a common framework through which to examine the effects of environmental stressors on adolescent adjustment. The model suggests that economic and neighborhood stressors influence youth adjustment via disruptions to parenting. Incorporating integrative developmental theory, we examined the degree to which parents’ cultural value orientations mitigated the effects of stressors on parenting disruptions and the degree to which environmental adversity qualified the effect of paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
170
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(184 citation statements)
references
References 48 publications
10
170
3
1
Order By: Relevance
“…Researchers consistently report that poverty creates a climate of risk for children that extends into adolescence (Brooks‐Gunn & Duncan, ), especially with regard to internalizing symptoms (e.g., Call et al., ; Wadsworth, Raviv, Santiago, & Etter, ). Consistent with this, family socioeconomic risk has been found to detrimentally affect the adjustment of Latino youth (e.g., Conger et al., ; Delgado, Killoren, & Updegraff, ; Parke et al., ; Z. E. Taylor, Larsen‐Rife, Conger, Widaman, & Cutrona, ; Z. E. Taylor et al., ; White, Liu, Nair, & Tein, ).…”
mentioning
confidence: 80%
“…Researchers consistently report that poverty creates a climate of risk for children that extends into adolescence (Brooks‐Gunn & Duncan, ), especially with regard to internalizing symptoms (e.g., Call et al., ; Wadsworth, Raviv, Santiago, & Etter, ). Consistent with this, family socioeconomic risk has been found to detrimentally affect the adjustment of Latino youth (e.g., Conger et al., ; Delgado, Killoren, & Updegraff, ; Parke et al., ; Z. E. Taylor, Larsen‐Rife, Conger, Widaman, & Cutrona, ; Z. E. Taylor et al., ; White, Liu, Nair, & Tein, ).…”
mentioning
confidence: 80%
“…The current investigation also extends work conducted by others. White, Liu, Nair, & Tein (2015) indicated that economic pressure was associated with higher levels of harsh parenting which was related to increases in adolescent externalizing behavior. Similarly, Ponnet (2014) investigated financial stress and found that parental depressive symptoms, parental conflict, and parenting mediated the association between financial stress and adolescent problem behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Since the initial supportive findings for the FSM, several other independent studies have replicated specific pathways within the model (see also Behnke et al, 2008; Conger et al, 2002; Gershoff et al, 2007; Mistry et al, 2008; Mistry, Lowe, Benner, & Chien, 2008; Mistry, Vandewater, Huston, & McLoyd, 2002; Parke et al, 2004; Scaramella, Sohr-Preston, Callahan, & Mirabile, 2008; Yeung, Linver, & Brooks-Gunn, 2002; Yoder & Hoyt, 2005). For example, White et al (2015) found that economic pressure was associated with increases in harsh parenting for Mexican origin mothers. Harsh parenting was related to increases in adolescent externalizing behavior.…”
Section: The Family Stress Modelmentioning
confidence: 99%
“…For example, many studies include economic hardship, parental emotional distress, and harsh or positive parenting, but may not account for economic pressure or couple conflict within the model. For instance, White, Liu, Nair, and Tein (2015) examined elements of the FSM from late childhood to middle adolescence in a sample of Mexican origin families. Although this study used a longitudinal design, it did not include all key pathways of the FSM and was focused on adolescents rather than younger children.…”
mentioning
confidence: 99%